ALTERNATIF PENGOLAHAN LIMBAH KOTORAN AYAM MENGGUNAKAN BLACK SOLDIER FLY (BSF) - Yayok Suryo Purnomo; Victoria Anggun Kristanti (EnviroUS, 2022)
Chicken manure is an organic waste that can be a source of pollution for the environment if it is not treated before being discharged into the environment. The treatment offered to overcome this is the bioconversion process, namely the overhaul of organic waste by a fermentation process carried out by living things, one of which is Black Soldier Fly (BSF) larvae. The aim of the study was to determine the amount of reduction that BSF larvae can do in treating chicken manure with variations of bioactivators and modification of feed rates and their effect on the growth of BSF larvae and content in BSF larvae. The optimal reduction results in chicken manure without bioactivator was 66.7%, with MOL Rice 60%, MOL Pineapple 62.2%, MOL Papaya 62.2%, and EM4 66.7%. The average increase in body length of BSF larvae was 0.7 cm and the average weight gain was 0.4 g. The best content of BSF larvae to be given as feed for laying hens II according to SNI is BSF larvae by giving chicken manure waste without variation.